2020
DOI: 10.1101/2020.03.04.974949
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mouse embryonic stem cells self-organize into trunk-like structures with neural tube and somites

Abstract: One sentence summary: A platform for generating trunk-like-structures with precursors of spinal cord, bone and muscle from stem cells in a dish Abstract: Post-implantation embryogenesis is a highly dynamic process comprising multiple lineage decisions and morphogenetic changes inaccessible to deep analysis in vivo. Mouse embryonic stem cells (mESCs) can form aggregates reflecting the post-occipital embryo (gastruloids), but lacking proper morphogenesis. Here we show that embedding of aggregates derived from mE… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
98
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(106 citation statements)
references
References 65 publications
8
98
0
Order By: Relevance
“…Upon exposure to external cues and morphogens, gastruloids show an intrinsic capability to polarize, elongate and pattern 11,12 . Strikingly, 3D gastruloids exhibit a multiaxial organization and spatiotemporal patterning of Hox genes 13 with signatures of somitogenesis 14, 15 . From in-vitro assays, it is evident that a combination of particular cell types is needed to generate lumen in the blastocyst 16 and establish an anterior-posterior axes prior gastrulation 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Upon exposure to external cues and morphogens, gastruloids show an intrinsic capability to polarize, elongate and pattern 11,12 . Strikingly, 3D gastruloids exhibit a multiaxial organization and spatiotemporal patterning of Hox genes 13 with signatures of somitogenesis 14, 15 . From in-vitro assays, it is evident that a combination of particular cell types is needed to generate lumen in the blastocyst 16 and establish an anterior-posterior axes prior gastrulation 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Somite formation is a rhythmic process that involves molecular oscillation and the expression of certain genes that pattern the embryo, collectively known as the molecular segmentation clock that has been widely characterized in several model systems and PSCs ( Diaz-Cuadros et al., 2020 ; Matsuda et al., 2020 ; Pourquie, 2003 ). The presence of an active segmentation clock in gastruloids similar to an in vivo embryo extends the power of this model system to characterize mammalian development ( van den Brink et al., 2020 ; Veenvliet et al, 2020 ). Nevertheless, the advent of blastoids and gastruloids from mESCs has opened new avenues to understand embryogenesis with wide application in biomedical discoveries especially for understanding developmental malformations.…”
Section: An Overview Of Self-organization Of Stem Cells To Form Embrymentioning
confidence: 75%
“…datasets provide evidence on the emergence of neural tube and somites recapitulating early organogenesis ( van den Brink et al., 2020 ; Veenvliet et al, 2020 ). Culturing mouse gastruloids with an underlying extracellular matrix led to the formation of structures resembling somites and neural tube ( van den Brink et al., 2020 ; Veenvliet et al, 2020 ), whereas another report suggested that mixing gastruloids and extra-endodermal cells can lead to the formation of the neural tube ( Bérenger-Currias et al, 2020 ). Recently, gastruloids have been generated from self-organizing hESCs, which can also differentiate to three germ layers ( Moris et al., 2020 ).…”
Section: An Overview Of Self-organization Of Stem Cells To Form Embrymentioning
confidence: 99%
See 2 more Smart Citations